Endometriosis: Molecular Pathophysiology and Recent Treatment Strategies-Comprehensive Literature Review - Marcin Sadłocha; Jakub Toczek; Katarzyna Major; Jakub Staniczek; Rafał Stojko (MDPI AG, 2024)
Endometriosis is an enigmatic disease, with no specific cause or trigger yet discovered. Major factors that may contribute to endometriosis in the pelvic region include environmental, epigenetic, and inflammatory factors. Most experts believe that the primary mechanism behind the formation of endometrial lesions is associated with Sampson's theory of "retrograde menstruation". This theory suggests that endometrial cells flow backward into the peritoneal cavity, leading to the development of endometrial lesions. Since this specific mechanism is also observed in healthy women, additional factors may be associated with the formation of endometrial lesions. Current treatment options primarily consist of medical or surgical therapies. To date, none of the available medical therapies have proven effective in curing the disorder, and symptoms tend to recur once medications are discontinued. Therefore, there is a need to explore and develop novel biomedical targets aimed at the cellular and molecular mechanisms responsible for endometriosis growth. This article discusses a recent molecular pathophysiology associated with the formation and progression of endometriosis. Furthermore, the article summarizes the most current medications and surgical strategies currently under investigation for the treatment of endometriosis.